El placer por la virtud: la acrasia en la Ética a Nicómaco - Cueto, Fernanda (2023)
Acrasia was the word used in Ancient Greece to refer to the phenomenon that occurs when a person is not able to act according to what her moral reason dictates. This article seeks to explain this phenomenon from an Aristotelian perspective. The thesis proposed is that, according to Aristotle, in order to carry out a virtuous action, knowledge is not enough, but one must also desire virtue. The acratic person is the one who, in spite of knowing what virtue consists of, does not feel pleasure in acting virtuously, because she has not cultivated the habit of acting according to her reason.